MicroRNAs: Pleiotropic Regulators in the Tumor Microenvironment - Yang, Ning; Zhu, Shan; Lv, Xinping; Qiao, Yuan; Liu, Yong-Jun; Chen, Jingtao (Frontiers in Immunology, 2018)
MicroRNAs (miRNAs) are small non-coding RNAs that typically inhibit the translation and stability of messenger RNAs (mRNAs). They are approximately 22 nucleotides long and control both physiological and pathological processes. Altered expression of miRNAs is often associated with human diseases. Thus, miRNAs have become important therapeutic targets, and some clinical trials investigating the effect of miRNA-based therapeutics in different types of diseases have already been conducted. The tumor microenvironment comprises cells such as infiltrating immune and cancer-associated endothelia cells (CAE) and cancer-associated fibroblasts CAFs), and all the components participate in the complicated crosstalk with tumor cells to affect tumor progression. Altered miRNAs expression in both these stromal and tumor cells could drive tumorigenesis. Thus, in this review, we discuss how aberrantly expressed miRNAs influence tumor progression; summarize the crosstalk between infiltrated immune cells, CAEs, CAFs, and tumor cells through miRNAs, and clarify the important roles of miRNAs in the tumor microenvironment, which may facilitate the clinical application of miRNA-based therapies.